The Impact of Dangerous Goods Transportation for Maritime Carrier Responsibility - Mounes, Hani (Journal of Legal Sciences, 2023)
The study dealt with The impact of dangerous goods Transportation for Maritime carrier responsibility, the study was exposed to the definition of dangerous goods. the study also dealt with the impact of IMDG code on the responsibility of the carrier, and the duties of the parties, as the study spotlights The duty of the carrier to prepare a compatible ship for dangerous goods transport, as well as the duty of the carrier to preserve the goods while highlighting to the difference in this obligation while transporting dangerous goods, and the study also reviewed the duties of the shipper, for example, his duty to inform the carrier with the dangerous nature of the goods and the role of IMDG code in dealing with the danger of these goods. the study also reached several recommendations, the importance to regulate the non- packaged goods as same with packaged goods, also the importance to accept dealing with dangerous goods in light of the acceptable risk, and the necessity of periodic updating of the lists of dangerous goods.